Performance studies, personal experience and knowledge: affirming personal experience as a resource in the study and creation of performance - Khala, Ayanda Kabelo (My University, 2012)
This research report entitled Performance Studies, Personal Experience and Knowledge: Affirming Personal Experience as a Resource in the Study and Creation of Performance explores the idea that theatre performance has within it the capacity to transform the theatre performer and consequently, the audience member and a greater society. This written component is derived from the observation of-as well as the participation in- two theatre-based case studies namely, Self, Play, Imagination and Story- a tertiary level performance studies course and Happy. Period. As in, FULL STOP!- an interactive theatre performance. Consequently, this report is practice-based research. The research analyses the use of personal experiences as resource material for theatre making within a South African context and provides a framework for the exploration of suitable methods for working through theatre and education to address personal transformation. This research offers a learning paradigm that affirms the use of personal story in creating theatre work and shows an example of how personal experience can play a role in addressing social issues through the interaction of theatre performers with each other and with audiences. This research finds, in its conclusion, that theatre that enhances the expression, ownership, and reflection of personal narrative can play a significant role in transformation.
M.A. University of the Witwatersrand, Faculty of Humanities (Dramatic Art), 2012